STUDI KESESUAIAN LAHAN TANAMAN TOMAT DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Yunita, Sari; Hermon, Dedi; Thesiwati, Aslan Sari (Pendidikan Geografi, 2013)
The purpose of this study were: 1) determine the characteristics of suitable land to plant tomatoes and knowing where the land units suitable for tomato plants in the Valley District Gumanti. Landform units that exist in the study area consists of 60 land units and samples taken only 8 land units only. Sampling technique was purposive random sampling is a sampling technique that captured data collection techniques used were in the form of descriptive tables analysts comparison between land characteristics (soil texture, slope, drainage, elevation, pH,) compared with the level of land suitability for tomato plants. The results showed that: (1) there are differences in land characteristics are soil texture, slope, drainage, elevation, pH, on each unit of land in the District Gumanti valley, (2) the presence of the suitability of land for crop diversity Tomato in the Valley District GumantiSatuanlahan Somewhat in accordance with the conditions and in accordance